The impact of maternal employment on children's weight: Evidence from the UK - Emla Fitzsimons; Benedetta Pongiglione (Elsevier, 2019)
Previous research shows that maternal employment is associated with higher children's body mass index (BMI). Using a large UK longitudinal birth cohort study of almost 20,000 children, we examine the effect of maternal employment during childhood (to age 14) on children's weight. We address the endogeneity of maternal employment by estimating household fixed effects models. We find that maternal employment has a positive effect on children's BMI and therefore on excess weight, and this is particularly the case for single mothers. We investigate potential pathways, including children's sedentary behavior and healthy eating behaviors, and find evidence of more sedentary behavior and poorer eating habits amongst children whose mothers are in employment. This is consistent with higher BMI levels amongst these children. Keywords: BMI, Maternal employment, Partnership status, Fixed effects, Sedentary behavior, Healthy eating